Synthesis of Vinylphenyl Oligomeric Silsesquioxane Based on MQ Silicone Resin - Li, Ru; Zhang, Baotan; Sun, Yongling; Liu, Bailing; Wang, Gongying (Asian Journal of Chemistry, 2012)
A novel vinylphenyl oligomeric silsesquioxane (VPOSS) based on MQ silicone resins were synthesised by cohydrolysis and polycondensation of phenyltriethyloxysilane, tetraethyloxysilane, 1,4-divinyltetramethyldisiloxane and hexamethyldisiloxane. The structure, morphology and properties of the developed copolymers were investigated by FTIR, DSC, XRD, 1H and 29Si NMR, GPC, TGA and SEM. The heat of fusion (DHf) measured for crystal melting was 21.27 J/g for VPOSS V. The results indicated that the cage and/or ladder structure and the decreasing content of M unit (mol %) in copolymers enhanced the thermal properties of the VPOSSs. The scanning electron microscopy images showed curved surface and lamellar fracture of VPOSS, which can be specialties of potential materials for connectivity and supporter of catalyst. Also, the most important applications are that multifunctional VPOSSs can be used as potential moieties for temperature resistance pressure sensitive adhensive and high performance liquid silicone rubber as light emitting diode encapsulation materials.